Assessment of Central Sleep Apnea Events in Children with Sleep-Disordered Breathing. (17th May 2022) - Kaplan, Alyson; Ulualp, Seckin O.
Abstract : Purpose . To determine the prevalence of central apnea (CA) events and central sleep apnea (CSA) in children with sleep-disordered breathing (SDB) and to assess the effect of tonsillectomy and adenoidectomy (TA) on CSA in children with obstructive sleep apnea (OSA). Material and Methods . The medical charts of children with SDB were reviewed to obtain information on past medical history, polysomnography (PSG) findings, and surgical management. Counts and indexes of obstructive apnea, obstructive hypopnea, and central apnea were evaluated before and after TA. The prevalence of CSA and the effect of age, gender, obesity, and comorbid conditions on CSA were assessed in children with SDB as well as in children with PSG proven OSA. Results . Seven hundred twelve children with SDB (age range: 1 to 18 yrs, mean: 5.8 ± 3.4 ) were identified. CA events occurred in 640 of 712 (89.5%) patients. Of the 712 patients, 315 (44.2%) met the criteria for the diagnosis of CSA. CSA was more prevalent in toddlers and preschoolers (p < 0.001 ). Obese children had a higher prevalence of CSA compared to nonobese children (p < 0.001 ). The prevalence of CSA in patients with OSA was 45.4%. The number of CA events, CAI, and OAHI after TA was less than that of before TA (p < 0.001 ). Residual CSA after TA occurred in 20 children (26%). Conclusion . Central apnea events and central sleep apnea occur in children who present to a pediatric otolaryngology clinic for evaluation of sleep disordered breathing. Central sleep apnea and obstructive sleep apnea both improve after tonsillectomy and adenoidectomy.